Upaya Peningkatan Hasil Belajar IPA Melalui Model Problem Based Learning ( PBL) Tipe Kooperatif Two Stay Two Stray ( TSTS ) - Retno Susiyani (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
Classroom action research in general aims to improve the learning outcomes of class IV learners on learning natural sciences (IPA) sub-energy and their changes, through the learning model problem based learning cooperative two stay two stray. The subject of the action recipient was 26 students of class IV of Purwoprajan II State Elementary School. Comparative descriptive data analysis techniques over each cycle experienced. Data validation techniques with source and method triangulation techniques. Each cycle consists of planning, action, observation, and reflection stages. Each cycle is carried out in two meetings by applying a learning model problem based learning cooperative two stay two stray. The presiklus evaluation was carried out on August 23, 2021 from the grade data showing that only 35% of students achieved KKM scores with an average accumulative score of 65. The first cycle was carried out on September 20, 2021 and October 11, 2021, in cycle 1 obtained the results of 17 people had reached KKM with a percentage of 65%. The average class is 72. There is an advanced cycle because researchers have a target of achieving classical completion of at least 85%. The second cycle will be held on October 25, 2021 and November 08, 2021. In cycle II, it was found that 96% of students were classically able to achieve KKM scores above 70 with an average score of 79.6. The results of the study concluded that the use of models problem based learning cooperative two stay two have increase student activity and has impact on improving student learning outcomes.